Front Cover: Effect of Regiochemistry and Methylation on the Anticancer Activity of a Ferrocene‐Containing Organometallic Nucleoside Analogue (ChemBioChem 17/2020). (13th August 2020) - Ismail, Media K.; Khan, Zahra; Rana, Marium; Horswell, Sarah L.; Male, Louise; Nguyen, Huy V.; Perotti, Alessio; Romero‐Canelón, Isolda; Wilkinson, Edward A.; Hodges, Nikolas J.; Tucker, James H. R.
Abstract : Iron works : A ferrocene derivative, one of a series of ferronucleosides designed by the Tucker group, shows micromolar toxicity in a range of cancer cell lines. Their latest research shows the importance to activity of having arms in adjacent positions, with the 1, 1'‐regioisomer much less active in bone cancer cell lines. On the other hand, N‐ or O‐methylation has much less of an effect; this rules out a conventional mechanism of action for a nucleoside, giving further weight to one that involves the iron centre. More information can be found in the full paper by N. J. Hodges, J. H. R. Tucker et al.